Peran Pendidikan Berkelanjutan Pada Era Gen-Z - Adhim, Assafrul Ali; Nugraheni, Nursiwi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The human population increases every year, forming several generations in line with the development of globalization. In the era of society 5.0, it is dominated by the millennial generation and Gen Z. These two generations have different characteristics from previous generations. This is because they were born, grew and developed along with the birth and development of digital technology. So, they are very dependent on technology, want something that is fast, comfortable and simple. This results in demoralization. Therefore, education is an important key in improving the quality of human resources. Continuous education is needed as an effort to improve human quality and welfare. Sustainable education requires educational development that is designed with the future in mind. The goal is to create quality, independent, advanced and modern humans. The aim of this article is to examine the role of sustainable education in the Gen Z era. The research method used is literature. The results are that sustainable education has a very important role in creating quality education, by providing character education, using electronic learning media, creating learning activities that are responsive, flexible and relevant, learning activities by choosing strategies, models and learning methods that are participant-oriented. educate and hone students' soft skills.